Dual-specificity protein phosphatase DUSP4 regulates response to MEK inhibition in BRAF wild-type melanoma - Gupta, Avinash; Towers, Christopher; Willenbrock, Frances; Brant, Roz; Hodgson, Darren Richard; Sharpe, Alan; Smith, Paul; Cutts, Anthony; Schuh, Anna; Asher, Ruth; Myers, Kevin; Love, Sharon; et al. (British journal of cancer, 2020)
Background Aiming to improve treatment options for BRAF wild-type melanoma, we previously conducted the DOC-MEK study of docetaxel with MEK inhibitor (MEKi) selumetinib or placebo, revealing trends to prolongation of progression-free survival (hazard ratio 0.75, P = 0.130), and improved response rates (32% vs 14%, P = 0.059) with docetaxel plus selumetinib. NRAS status did not associate with outcome. Here, the aim was to identify novel biomarkers of response to MEKi. Methods A MEK 6 gene signature was quantified using NanoString and correlated with clinical outcomes. Two components of the gene signature were investigated by gene silencing in BRAF/NRAS wild-type melanoma cells. Results In melanomas of patients on the selumetinib but not the placebo arm, two gene signature components, dual-specificity protein phosphatase 4 (DUSP4) and ETS translocation variant 4 (ETV4), were expressed more highly in responders than non-responders. In vitro, ETV4 depletion inhibited cell survival but did not influence sensitivity to MEKi selumetinib or trametinib. In contrast, DUSP4-depleted cells showed enhanced cell survival and increased resistance to both selumetinib and trametinib. Conclusions ETV4 and DUSP4 associated with clinical response to docetaxel plus selumetinib. DUSP4 depletion induced MEKi resistance, suggesting that DUSP4 is not only a biomarker but also a mediator of MEKi sensitivity. Clinical Trial Registration DOC-MEK (EudraCT no: 2009-018153-23).